Polarizing plate, polarizing plate, method for manufacturing polarizing
By applying the protective film to the polarizer and using active energy ray curing adhesive, the problem of insufficient bonding between the polarizer and the protective film is solved, and higher optical performance and temperature stability are achieved.
Patent Information
- Application Number
- CN202411020598.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-02
- Filing Date
- 2024-07-29
- Publication Date
- 2025-02-14
AI Technical Summary
In the prior art, the adhesive force between the polarizer and the protective film is insufficient, making it difficult to meet the needs of high optical characteristics and temperature stability.
By bonding the protective film to one or both sides of the polarizer and forming an adhesive layer with an active energy ray curing adhesive, the bonding force between the polarizer and the protective film is improved.
The adhesion between the polarizer and the protective film is significantly improved, and its stability and optical properties under temperature changes are enhanced.
Smart Images

Figure CN119439345A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing film, a polarizing plate, a method for producing a polarizing film, and a method for producing a polarizing plate. Background Art
[0002] A polarizer obtained by adsorbing a dichroic pigment on a polyvinyl alcohol-based resin film and orienting the film is known. Patent Document 1 states that if the degree of boric acid crosslinking of the polarizer is increased, high optical properties can be obtained, but the film is easily shrunk due to temperature changes. A method for producing a polarizing film that increases the degree of boric acid crosslinking and is not easily shrunk due to temperature changes is described. In addition, a protective film is attached to one or both sides of a polarizer using an adhesive to use as a polarizing plate.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2022-136978 Summary of the invention
[0006] Problem that the invention aims to solve
[0007] There is a demand for further improvement in the adhesion between a polarizing plate and a protective film obtained by adsorbing and aligning a dichroic dye on a polyvinyl alcohol-based resin film.
[0008] Solutions for solving problems
[0009] The present invention includes the following technical solutions.
[0010] [Invention 1]
[0011] A polarizing plate obtained by adsorbing a dichroic dye on a polyvinyl alcohol-based resin film and orienting the film.
[0012] The boric acid crosslinking degree of the polarizer is 3.3 or less,
[0013] Visibility correction single unit transmittance is more than 40%,
[0014] The visibility-corrected polarization degree is above 99.98%.
[0015] [Invention 2]
[0016] A polarizing plate comprising the polarizing plate according to [Invention 1], and a protective film on at least one surface of the polarizing plate.
[0017] [Invention 3]
[0018] The polarizing plate according to [Invention 2] further comprises a laminating layer for laminating the polarizer and the protective film.
[0019] The bonding layer is a layer obtained by curing an active energy ray-curable adhesive.
[0020] [Invention 4]
[0021] A method for producing a polarizing plate, wherein the polarizing plate is obtained by adsorbing a dichroic pigment on a polyvinyl alcohol-based resin film and orienting the film, and the method comprises the following steps:
[0022] a dyeing step of dyeing the polyvinyl alcohol-based resin film with a dichroic pigment;
[0023] a cross-linking step of cross-linking the polyvinyl alcohol-based resin film after the dyeing step; and
[0024] a drying step of drying the polyvinyl alcohol-based resin film after the cross-linking step,
[0025] The aforementioned cross-linking process has the following steps:
[0026] a first cross-linking step of immersing the polyvinyl alcohol-based resin film in a first cross-linking bath having a boric acid content of 4.0 parts by mass or less relative to 100 parts by mass of water; and
[0027] The second cross-linking step is to immerse the polyvinyl alcohol-based resin film after the first cross-linking step in a second cross-linking bath containing 3.5 parts by mass or less of boric acid relative to 100 parts by mass of water.
[0028] [Invention 5]
[0029] The method for producing a polarizing plate according to [Invention 4], wherein the temperature of the first cross-linking bath is 60° C. or lower, and the temperature of the second cross-linking bath is 45° C. or lower.
[0030] [Invention 6]
[0031] A method for manufacturing a polarizing plate comprises the following steps:
[0032] A step of manufacturing a polarizing plate by the manufacturing method according to [Invention 4] or [Invention 5]; and a step of laminating a protective film on one or both surfaces of the polarizing plate via a laminating layer.
[0033] Effects of the Invention
[0034] According to the polarizing plate of the present invention, it is possible to improve the adhesion with the protective film. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is a schematic cross-sectional view showing a polarizing plate of the present invention.
[0036] Figure 2 This is a cross-sectional view schematically showing an example of the method for producing a polarizing plate according to the present invention and a polarizing plate producing apparatus used therein.
[0037] Description of Reference Numerals
[0038] 10…Polarizing plate
[0039] 11…Polarizer
[0040] 12…Adhesive layer
[0041] 13…Protective film
[0042] 13a…first protective film
[0043] 13b…Second protective film
[0044] 14…Swelling bath
[0045] 15…dye bath
[0046] 16a…First cross-linking bath
[0047] 16b…Second crosslinking bath
[0048] 17…Color-enhancing bath
[0049] 18…Cleaning Bath
[0050] 19…Drying oven
[0051] 20…Polarizing plate manufacturing device
[0052] 21…raw film
[0053] 22…Roller
[0054] 30~52、60、61…guide roller
[0055] 70~77…Roller DETAILED DESCRIPTION
[0056] Hereinafter, embodiments of the present invention will be described in detail. It should be noted that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made within the scope of the present invention.
[0057] <Polarizing Plate>
[0058] Polarizer 11 is obtained by adsorbing dichroic pigment on polyvinyl alcohol resin film and oriented. As polyvinyl alcohol resin, for example, a resin obtained by saponifying polyvinyl acetate resin can be used. The saponification degree of polyvinyl acetate resin is preferably 85 mol% or more, more preferably 90 mol% or more, and further preferably 99 mol% or more.
[0059] As the polyvinyl acetate resin, for example, polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith can be used. Examples of other monomers copolymerizable therewith include unsaturated carboxylic acids, olefins, vinyl ethers, and unsaturated sulfonic acids.
[0060] The degree of polymerization of the polyvinyl alcohol-based resin is preferably 1,000 or more and 10,000 or less, and more preferably 1,500 or more and 5,000 or less.
[0061] The polyvinyl alcohol-based resin may be modified. Examples of the modified polyvinyl alcohol-based resin include polyvinyl formal, polyvinyl acetal, and polyvinyl butyral modified with aldehydes.
[0062] Examples of the dichroic pigment include iodine and water-soluble dichroic dyes.
[0063] The thickness of the polarizing plate 11 is not particularly limited, but is 1 μm or more, preferably 5 μm or more, more preferably 10 μm or more, and further preferably 20 μm or more, and is 50 μm or less, preferably 30 μm or less.
[0064] The boric acid crosslinking degree of the polarizer 11 is 3.3 or less, preferably 3.2 or less. From the viewpoint of improving the polarization degree, the boric acid crosslinking degree is 2.5 or more, preferably 2.8 or more, and more preferably 3.0 or more.
[0065] In the polarizer 11 of this embodiment, the dichroic pigment is adsorbed on the polyvinyl alcohol resin film and oriented, and the degree of crosslinking with boric acid is 3.3 or less. If the degree of crosslinking with boric acid is 3.3 or less, the number of sites where the hydroxyl groups of the polyvinyl alcohol resin are crosslinked with boric acid becomes relatively small. In other words, the amount of hydroxyl groups in the polyvinyl alcohol resin that are not crosslinked with boric acid becomes relatively large. Therefore, Figure 1 As shown, when the polarizer 11 and the protective film 13 are bonded together by means of an adhesive, the interaction between the hydroxyl group of the polyvinyl alcohol resin and the adhesive can be increased. Thus, the adhesion between the polarizer 11 and the adhesive layer 12 can be improved, and therefore, the adhesion between the polarizer 11 and the protective film 13 can be improved.
[0066] The visibility-corrected single body transmittance is 40% or more, preferably 41% or more, more preferably 42% or more, and further preferably 43% or more.
[0067] The visibility-corrected polarization degree is 99.9% or more, preferably 99.95% or more, and more preferably 99.98% or more.
[0068] The methods for measuring the boric acid crosslinking degree, the visibility correction monomer transmittance, and the visibility correction polarization degree are described below.
[0069] <Polarizing Plate>
[0070] like Figure 1 As shown, the polarizing plate 10 can be obtained by laminating the protective film 13 on at least one side of the polarizing plate 11 via a laminating layer (e.g., an adhesive). That is, the polarizing plate 10 includes the polarizing plate 11, the protective film 13, and the adhesive layer 12 for laminating the polarizing plate 11 and the protective film 13.
[0071] As the protective film 13 , a known transparent protective film can be used.
[0072] Specific examples of the protective film 13 include cellulose acetate resin films such as cellulose triacetate and cellulose diacetate; polyester resin films such as polyethylene terephthalate, polyethylene naphthalate and polybutylene terephthalate; polycarbonate resin films, cycloolefin resin films, acrylic resin films, polypropylene resin and other chain olefin resin films, etc.
[0073] The thickness of the protective film 13 is not particularly limited, but is 1 μm or more, preferably 10 μm or more, and more preferably 30 μm or more from the viewpoint of operability in the manufacturing process. In addition, from the viewpoint of thin filmization of the polarizing plate, it is 200 μm or less, preferably 100 μm or less, more preferably 80 μm or less, and further preferably 60 μm or less.
[0074] As the laminating layer used for laminating the polarizer 11 and the protective film 13, an adhesive layer or a pressure-sensitive adhesive layer can be cited. The adhesive layer is formed of a pressure-sensitive adhesive, and the pressure-sensitive adhesive layer is formed of a pressure-sensitive adhesive. As the pressure-sensitive adhesive, for example, an active energy ray-curable adhesive such as an ultraviolet-curable adhesive; an aqueous solution of a polyvinyl alcohol-based resin, or an aqueous solution mixed with a crosslinking agent, a urethane-based emulsion adhesive, and other water-based adhesives can be cited.
[0075] Among these, active energy ray-curable adhesives are preferred. In other words, the adhesive layer 12 included in the polarizing plate 10 is preferably a layer obtained by curing an active energy ray-curable adhesive.
[0076] The active energy ray curing adhesive is an adhesive cured by irradiation with active energy rays such as ultraviolet rays, visible rays, X-rays or electron beams. The active energy ray curing adhesive has adhesiveness before irradiation with active energy rays, and therefore, is easily adhered to the surface of the polarizer 11 and the protective film 13. In addition, the adhesion can be adjusted by the irradiation amount of the active energy ray.
[0077] The thickness of the adhesive layer 12 is not particularly limited, and is 0.01 μm or more, preferably 0.1 μm or more, more preferably 0.5 μm or more, and further preferably 1 μm or more. In addition, it is 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less. The thickness of the adhesive layer 12 when an active energy ray-curable adhesive is used as an adhesive refers to the thickness of the layer obtained by curing the active energy ray-curable adhesive.
[0078] In order to improve the adhesion between the polarizer 11 and the protective film 13, the bonding surface of at least one of the polarizer 11 and the protective film 13 may be subjected to surface treatment. Examples of the surface treatment include corona treatment, flame treatment, plasma treatment, ultraviolet irradiation, primer coating treatment, and saponification treatment.
[0079] <Method for Manufacturing Polarizing Plate>
[0080] like Figure 2 As shown in FIG. 1 , the polarizer 11 is manufactured using a polarizer manufacturing device 20. The polarizer manufacturing device 20 has a treatment bath containing a treatment liquid. Specifically, the polarizer manufacturing device 20 has a swelling bath 14, a dyeing bath 15, a first cross-linking bath 16a, a second cross-linking bath 16b, a color correction bath 17, and a cleaning bath 18. In addition, the polarizer manufacturing device 20 has a drying furnace 19, guide rollers 30 to 52, 60, 61, and rollers 70 to 77.
[0081] When the polarizing plate 11 is produced, a raw material of a polyvinyl alcohol-based resin, that is, an unstretched raw material film 21 is used. The raw material film 21 is wound around a roll 22 .
[0082] First, the original film 21 is unwound from the roller 22 and conveyed along the film conveying path of the polarizing plate manufacturing device 20. Next, a treatment process is performed in which the original film 21 is immersed in a treatment bath containing a treatment liquid and then pulled out. Furthermore, a long polarizing plate 11 can be continuously manufactured by performing a drying process. It should be noted that Figure 2 The arrow in shows the conveying direction of the film. The above-mentioned treatment bath is also called a treatment tank.
[0083] Examples of the treatment liquid include a swelling liquid, a dyeing liquid, a first cross-linking liquid, a second cross-linking liquid, a color correction liquid, and a cleaning liquid.
[0084] The process of bringing the swelling liquid into contact with the original film 21 to perform swelling treatment is set as the swelling process. The process of bringing the dyeing liquid into contact with the film after the swelling treatment to perform dyeing treatment is set as the dyeing process. The process of bringing the first cross-linking liquid into contact with the film after the dyeing treatment to perform the first cross-linking treatment is set as the first cross-linking process. The process of bringing the second cross-linking liquid into contact with the film after the first cross-linking treatment to perform the second cross-linking treatment is set as the second cross-linking process. The process of bringing the color correction liquid into contact with the film after the second cross-linking treatment to perform the color correction treatment is set as the color correction process. The process of bringing the cleaning liquid into contact with the film after the color correction treatment to perform the cleaning treatment is set as the cleaning process.
[0085] The guide rollers 30 to 52, 60, and 61 are used to support the film being transported or to change the transport direction of the film. The rollers 70 to 77 are used to press / clamp the film being transported, and to apply driving force to the film by their rotation. Furthermore, by arranging the rollers 70 to 77 before and after each treatment bath, a circumferential speed difference can be made between the rollers 70 to 77 arranged before and after it in any one or more treatment baths. By making the circumferential speed difference between the rollers 70 to 77, inter-roller stretching can be performed. That is, between a series of treatment processes, a uniaxial stretching process can be performed as a stretching process.
[0086] The polarizing plate manufacturing apparatus 20 uses guide rollers 30 to 52, 60, 61 and nip rollers 70 to 77 to convey the film, and sequentially passes through a swelling bath 14, a dyeing bath 15, a first crosslinking bath 16a, a second crosslinking bath 16b, a color correction bath 17 and a cleaning bath 18 provided on the film conveying path, and finally passes through a drying furnace 19.
[0087] The guide rollers 30 to 52, 60, 61 and the nip rollers 70 to 77 can be arranged before and after each treatment bath or in the treatment bath. Thus, the film can be efficiently introduced / immersed into the treatment bath and drawn out from the treatment bath. For example, by arranging one or more guide rollers in each treatment bath and conveying the film along these guide rollers, the film can be efficiently immersed in each treatment bath.
[0088] Hereinafter, each processing step will be described in detail.
[0089] (Swelling process)
[0090] The swelling step is a step of bringing a swelling liquid into contact with the original film 21 to perform swelling treatment.
[0091] In the swelling step, foreign matter may be removed from the surface of the original film 21, plasticizer may be removed from the original film 21, dyeability may be imparted, the original film 21 may be plasticized, and the like may be performed.
[0092] The processing conditions are determined within a range in which undesirable conditions such as extreme dissolution and devitrification of the original film 21 do not occur.
[0093] like Figure 2 As shown, in the swelling step, the original film 21 is continuously rolled out from the roll 22 and conveyed along the film conveying path. Furthermore, the original film 21 is immersed in the swelling bath 14 for a predetermined time and then pulled out.
[0094] like Figure 2 As shown, from the time when the original film 21 is unwound to the time when it is immersed in the swelling bath 14, the original film 21 is conveyed along the film conveying path constructed by the guide rollers 60, 61 and the nip roller 70. During the swelling treatment, the original film 21 is conveyed along the film conveying path constructed by the guide rollers 30 to 32 and the nip roller 71.
[0095] Pure water can be used as the swelling liquid of the swelling bath 14. In addition, aqueous solutions of boric acid (Japanese Patent Laid-Open No. 10-153709), chlorides (Japanese Patent Laid-Open No. 06-281816), inorganic acids, inorganic salts, water-soluble organic solvents, alcohols, etc. can also be used. The concentration in the aqueous solution can be set to a range of 0.01% by mass or more and 10% by weight or less.
[0096] The temperature of the swelling bath 14 is, for example, 10° C. or higher, or preferably 20° C. or higher, and is 50° C. or lower, or preferably 40° C. or lower.
[0097] The immersion time of the original film 21 is 10 seconds or more, preferably 20 seconds or more, and is 300 seconds or less, preferably 200 seconds or less.
[0098] During the swelling treatment, the original film 21 may swell in the width direction, and wrinkles may be generated in the film. As a means for removing the wrinkles and conveying the film, rollers with a width expansion function such as expansion rollers, spiral rollers, and medium-high rollers may be used as guide rollers 30 to 32. In addition, other width expansion devices such as a cloth guide, a flexure steel, and a tenter clamp may be used.
[0099] As another means for suppressing the generation of wrinkles, stretching treatment can be mentioned. For example, uniaxial stretching treatment can be performed in the swelling bath 14 by utilizing the difference in peripheral speed between the rollers 70 and 71. These means are also collectively referred to as "means for suppressing wrinkles".
[0100] During the swelling treatment, the film also swells and expands along the conveying direction of the original film 21. When the original film 21 is not actively stretched, it is preferable to suppress the relaxation of the original film 21 in the conveying direction. For example, it is preferable to adopt means such as controlling the speed of the rollers 70 and 71 arranged before and after the swelling bath 14. In addition, it is also preferable to stabilize the conveyance of the film in the swelling bath 14. For example, it is also useful to control the water flow in the swelling bath 14 by spraying in water or to use an EPC device (Edge Position Control device: a device that detects the end of the film and prevents the film from meandering).
[0101] like Figure 2 As shown, the film drawn out from the swelling bath 14 passes through the guide roller 32 , the nip roller 71 , and the guide roller 33 in sequence, and is introduced into the dyeing bath 15 .
[0102] (Dyeing process)
[0103] The dyeing step is a step of dyeing the film after the swelling treatment by bringing a dyeing liquid into contact with the film. Specifically, in the dyeing step, the dichroic dye is adsorbed and oriented on the polyvinyl alcohol-based resin film after the swelling treatment.
[0104] like Figure 2 As shown, in the dyeing process, the film after swelling treatment is conveyed along the film conveying path constructed by the nip roller 71, the guide rollers 33 to 36 and the nip roller 72. Then, the film is immersed in the dyeing bath 15 for a predetermined time and then pulled out.
[0105] In order to improve the dyeability of the dichroic pigment, the film provided in the dyeing process is preferably a film that has been subjected to at least some degree of uniaxial stretching. Alternatively, it is preferred that the uniaxial stretching is performed during the dyeing process instead of or in addition to the uniaxial stretching before the dyeing process.
[0106] As the dichroic dye, for example, iodine etc. When iodine is used as the dichroic dye, the dyeing solution of the dye bath 15 can be, for example, an aqueous solution having a mass ratio of iodine / potassium iodide / water = 0.003 to 0.3 / 0.1 to 20 / 100.
[0107] Other iodides such as zinc iodide may be used instead of potassium iodide, or potassium iodide and other iodides may be used in combination. In addition, compounds other than iodides such as boric acid, zinc chloride, and cobalt chloride may coexist.
[0108] When boric acid is added, it is distinguished from the cross-linking treatment described later in that iodine is contained. If the aqueous solution contains 0.003 parts by mass or more of iodine relative to 100 parts by mass of water, it can be regarded as the dyeing bath 15 .
[0109] The temperature of the dye bath 15 when the film is immersed is 10° C. or higher, preferably 20° C. or higher, and is 50° C. or lower, preferably 40° C. or lower.
[0110] The immersion time of the film is 10 seconds or more, preferably 30 seconds or more, and is 600 seconds or less, preferably 300 seconds or less.
[0111] During the dyeing step, the film may be uniaxially stretched. In addition, wrinkle suppression measures may be taken.
[0112] exist Figure 2 In the example shown, the film drawn out from the dyeing bath 15 is introduced into the first cross-linking bath 16 a by passing through the guide roller 36 , the nip roller 72 , and the guide roller 37 in sequence.
[0113] (Cross-linking process)
[0114] The cross-linking step is a step of bringing a cross-linking liquid into contact with the dyed film to perform a cross-linking treatment. One of the purposes of the cross-linking step is water resistance based on cross-linking.
[0115] The cross-linking step includes a first cross-linking step and a second cross-linking step.
[0116] (First Cross-linking Step)
[0117] like Figure 2 As shown, in the first crosslinking step, the dyed film is conveyed along a film conveying path constructed by the nip roller 72, guide rollers 37 to 40, and nip roller 73. The film is immersed in the first crosslinking bath 16a for a predetermined time and then withdrawn.
[0118] The first cross-linking bath 16a may be a solution obtained by dissolving a cross-linking agent in a solvent. A boron compound is used as the cross-linking agent. A specific example of the boron compound is boric acid.
[0119] In addition, as a boron compound, borax may be contained on the basis of containing boric acid. In addition, compounds other than boron compounds may be contained on the basis of containing boric acid. Compounds other than boron compounds include, for example, glyoxal, glutaraldehyde, etc. These may be one or more in combination.
[0120] The first crosslinking liquid contains 4.0 parts by mass or less of boric acid relative to 100 parts by mass of water, preferably 3.7 parts by mass or less, more preferably 3.5 parts by mass or less, and further preferably 3.3 parts by mass or less. The first crosslinking liquid contains 1 part by mass or more of boric acid relative to 100 parts by mass of water, preferably 1.5 parts by mass or more.
[0121] When the dichroic dye used in the dyeing treatment is iodine, the first crosslinking liquid preferably contains iodide in addition to boric acid. The amount of iodide can be, for example, 1 part by mass or more and 20 parts by mass or less relative to 100 parts by mass of water.
[0122] Examples of the iodide include potassium iodide, zinc iodide, etc. In addition, a compound other than the iodide, for example, zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, sodium sulfate, etc., may coexist.
[0123] In the first cross-linking step, the concentrations of the boric acid and the iodide in the first cross-linking solution and the temperature of the first cross-linking bath 16 a can be appropriately selected.
[0124] The first cross-linking liquid may be, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1 to 4.0 / 1 to 20 / 100.
[0125] The temperature of the first cross-linking bath 16a when the film is immersed is 40°C or higher, preferably 50°C or higher, and is 70°C or lower, preferably 60°C or lower, and more preferably 58°C or lower.
[0126] The immersion time of the film is 10 seconds or more, preferably 20 seconds or more, more preferably 30 seconds or more, and is 600 seconds or less, preferably 300 seconds or less, more preferably 100 seconds or less, and further preferably 50 seconds or less.
[0127] (Second Crosslinking Step)
[0128] like Figure 2 As shown, in the second crosslinking step, the film after the first crosslinking treatment is conveyed along a film conveying path constructed by the nip roller 73, the guide rollers 41 to 44 and the nip roller 74. The film is immersed in the second crosslinking bath 16b for a predetermined time and then withdrawn.
[0129] The second crosslinking liquid contains 3.5 parts by mass or less of boric acid relative to 100 parts by mass of water, preferably 3.0 parts by mass or less, more preferably 2.8 parts by mass or less, and further preferably 2.5 parts by mass or less. The second crosslinking liquid contains 1 part by mass or more of boric acid relative to 100 parts by mass of water, preferably 1.5 parts by mass or more.
[0130] From the viewpoint of being able to adjust the crosslinking degree of the polarizer to the above range, it is preferred that the second crosslinking liquid has a smaller boric acid content relative to 100 parts by mass of water than the first crosslinking liquid.
[0131] In the second cross-linking step, the concentrations of the boric acid and the iodide in the second cross-linking solution and the temperature of the second cross-linking bath 16 b can be appropriately selected.
[0132] The second crosslinking liquid may be, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1 to 3.5 / 1 to 20 / 100.
[0133] The temperature of the second cross-linking bath 16b when the film is immersed is 20°C or higher, preferably 30°C or higher, and is 60°C or lower, preferably 50°C or lower, and more preferably 45°C or lower.
[0134] From the viewpoint of increasing the width reduction of the film and, as a result, increasing the degree of polarization, the temperature of the second cross-linking bath 16 b when the film is immersed is preferably lower than the temperature of the first cross-linking bath 16 a .
[0135] The immersion time of the film is 1 second or longer, and from the viewpoint of being able to adjust the crosslinking degree of the polarizer to the above range, it is 30 seconds or shorter, preferably 20 seconds or shorter, and more preferably 10 seconds or shorter.
[0136] The immersion time of the film is preferably the same as or shorter than that in the first cross-linking step. For example, it is preferably shorter than that in the first cross-linking step by 25 seconds or more.
[0137] In the first cross-linking step and the second cross-linking step, the film can also be uniaxially stretched. In addition, a means for suppressing wrinkles can be provided.
[0138] like Figure 2 As shown, the film drawn out from the second cross-linking bath 16 b passes through the guide roller 44 , the nip roller 74 , and the guide roller 45 in sequence, and is introduced into the color correction bath 17 .
[0139] (Coloring process)
[0140] The color correction step is a step of bringing a color correction liquid into contact with the film after the second cross-linking treatment to perform a color correction treatment. One of the purposes of the color correction step is to adjust the hue.
[0141] like Figure 2 As shown, in the color correction step, the film after the second crosslinking treatment is conveyed along a film conveying path constructed by the nip roller 74, the guide rollers 45 to 48, and the nip roller 75. The film is immersed in the color correction bath 17 for a predetermined time and then withdrawn.
[0142] As the color-replenishing solution, a solution obtained by dissolving a crosslinking agent in a solvent can be used in the same manner as the crosslinking solution. As the crosslinking agent, for example, boron compounds, glyoxal, glutaraldehyde, etc. can be listed. As the boron compound, boric acid, borax, etc. can be listed. They can be one kind, or two or more kinds can be used in combination. As the solvent, for example, water can be used, and an organic solvent compatible with water can also be included.
[0143] As the color-replenishing solution, for example, an aqueous solution containing 1 to 3 parts by mass of a boron compound such as boric acid relative to 100 parts by mass of water can be used. Preferably, an aqueous solution containing 1.5 to 3 parts by mass is used. When the dichroic pigment used in the dyeing process is iodine, the color-replenishing solution preferably contains an iodide in addition to boric acid.
[0144] The amount of the iodide can be, for example, 1 part by mass or more and 20 parts by mass or less relative to 100 parts by mass of water.
[0145] Examples of the iodide include potassium iodide, zinc iodide, etc. In addition, a compound other than the iodide, for example, zinc chloride, cobalt chloride, zirconium chloride, sodium thiosulfate, potassium sulfite, sodium sulfate, etc., may coexist.
[0146] In the color correction treatment, the concentrations of boric acid and iodide in the color correction solution and the temperature of the color correction bath 17 can be appropriately selected.
[0147] As the color-correcting solution, for example, an aqueous solution having a mass ratio of boric acid / potassium iodide / water=1 to 3.5 / 1 to 20 / 100 can be used.
[0148] The temperature of the color correction bath 17 when the film is immersed is 20° C. or higher, preferably 30° C. or higher, and is 60° C. or lower, preferably 50° C. or lower, and more preferably 45° C. or lower.
[0149] The immersion time of the film is 1 second or longer, and is 30 seconds or shorter, preferably 20 seconds or shorter, and more preferably 10 seconds or shorter.
[0150] The crosslinking treatment and the color correction treatment may be performed multiple times, usually 2 to 5 times. In this case, the composition and temperature of each crosslinking bath and each color correction bath used may be the same or different.
[0151] In the color correction step, the film may be uniaxially stretched. In addition, a means for suppressing wrinkles may be provided.
[0152] exist Figure 2 In the example shown, the film drawn out from the color correction bath 17 is introduced into the cleaning bath 18 through the guide roller 48, the nip roller 75, and the guide roller 49 in this order.
[0153] (Cleaning process)
[0154] The cleaning step is a step of cleaning the film after the color correction treatment by contacting the cleaning liquid. The cleaning step is performed for the purpose of removing excess chemicals such as boric acid and iodine attached to the polyvinyl alcohol resin film.
[0155] like Figure 2As shown, in the cleaning step, the film after the color correction treatment is conveyed along a film conveying path constructed by the nip roller 75, the guide rollers 49 to 52, and the nip roller 76. Then, the film is immersed in the cleaning bath 18 for a predetermined time and then pulled out.
[0156] As a cleaning liquid used in the cleaning step, water such as pure water can be mentioned.
[0157] The cleaning step may be performed by spraying the cleaning solution onto the film in a shower manner, or by combining immersion in the cleaning bath 18 and spraying the cleaning solution, instead of immersing the film in the cleaning bath 18 .
[0158] The temperature of the cleaning bath 18 during the cleaning treatment is preferably 2° C. or higher and 40° C. or lower, and the immersion time of the film is preferably 1 second or higher and 120 seconds or lower.
[0159] During the washing step, the film may be uniaxially stretched. In addition, wrinkle suppression measures may be taken.
[0160] exist Figure 2 In the example shown, the film drawn out from the cleaning bath 18 passes through the guide roller 52 and the nip roller 76 in this order and is introduced into the drying furnace 19 .
[0161] (Stretching process)
[0162] As described above, the original film 21 is subjected to a uniaxial stretching treatment by a wet method or a dry method between the above-mentioned series of treatment steps, that is, before or after any one or more of the treatment steps or during the treatment steps.
[0163] The specific method of uniaxial stretching treatment can be, for example, inter-roll stretching in which a difference in peripheral speed exists between two rollers constituting a film conveying path, for example, two rollers arranged before and after a treatment bath, and longitudinal uniaxial stretching is performed. Alternatively, hot roll stretching, tenter stretching, etc. as described in Japanese Patent No. 2731813 can be used. Among these, inter-roll stretching is preferably performed.
[0164] The uniaxial stretching step may be performed multiple times until a polarizing plate is obtained from the original film 21. As described above, the stretching treatment is also advantageous in suppressing the generation of wrinkles in the film.
[0165] The final cumulative stretching ratio of the polarizer based on the original film 21 is preferably 4.5 times or more and 7 times or less, and more preferably 5 times or more and 6.5 times or less. The stretching process can be performed in any treatment process, and when the stretching process is performed by two or more treatment processes, the stretching process can be performed in any treatment process.
[0166] (Drying process)
[0167] After the washing step, it is preferred to perform a treatment for drying the polyvinyl alcohol-based resin film.
[0168] like Figure 2 As shown, the method of drying the film is not particularly limited, but it is preferably carried out using a drying furnace 19. The drying furnace 19 can be a drying furnace equipped with a hot air dryer, for example.
[0169] The drying temperature is, for example, 30°C or higher, preferably 50°C or higher, more preferably 60°C or higher, and further preferably 70°C or higher. Also, it is 100°C or lower, preferably 90°C or lower, and more preferably 80°C or lower.
[0170] The drying time is, for example, more than 30 seconds, preferably more than 50 seconds, more preferably more than 80 seconds. In addition, it is less than 600 seconds, preferably less than 300 seconds, more preferably less than 200 seconds. The process of drying the polyvinyl alcohol resin film can also be carried out using a far infrared heater.
[0171] The obtained polarizing plate 11 may be successively wound up on a winding roll to be in a roll form, or may be directly provided to a polarizing plate production step, that is, a step of laminating a protective film on one or both surfaces of the polarizing plate without being wound up.
[0172] <Method for Manufacturing Polarizing Plate>
[0173] The method for producing the polarizing plate 10 includes: a step of producing the polarizing plate 11 by the above method; and a step of laminating the protective film 13 to one or both surfaces of the obtained polarizing plate 11 via a laminating layer.
[0174] like Figure 1 As shown, in the laminating step, it is preferable to form the adhesive layer 12 using an active energy ray-curable adhesive (hereinafter also simply referred to as “adhesive”).
[0175] In the laminating step, an adhesive is applied onto the protective film 13. The adhesive can be applied using, for example, a known bar coater. The thickness of the applied adhesive is not particularly limited, and can be, for example, 0.1 μm or more and 10 μm or less.
[0176] Next, the polarizing plate 11 is bonded to the adhesive-coated surface of the protective film 13. The bonding of the polarizing plate 11 can be performed using, for example, a roller. The surface of the polarizing plate 11 may be subjected to a surface treatment such as a corona treatment in advance.
[0177] Next, ultraviolet rays are irradiated from the protective film 13 side to polymerize and cure the adhesive.
[0178] Through the above steps, the polarizing plate 10 in which the protective film 13 is bonded to one or both surfaces of the polarizer 11 via the adhesive layer 12 can be obtained.
[0179] like Figure 2 As shown, in the manufacturing method of the polarizer 11 of the present embodiment, as a cross-linking process, there are a first cross-linking process and a second cross-linking process. In the first cross-linking process, a first cross-linking bath 16a in which the content of boric acid is less than 4.0 parts by mass relative to 100 parts by mass of water is used. In the second cross-linking process, a second cross-linking bath 16b in which the content of boric acid is less than 3.5 parts by mass relative to 100 parts by mass of water is used.
[0180] The first cross-linking step and the second cross-linking step both use a cross-linking bath with a relatively low boric acid content. Therefore, according to the manufacturing method of the polarizer 11 of the present embodiment, it is easy to manufacture a polarizer 11 with a boric acid cross-linking degree of 3.3 or less. In addition, by reducing the boric acid content of the second cross-linking bath 16b compared to the first cross-linking bath 16a, the polarizer 11 with a boric acid cross-linking degree of 3.3 or less can be efficiently manufactured.
[0181] Furthermore, by setting the temperature of the first cross-linking bath to 60° C. or less and the temperature of the second cross-linking bath to 45° C. or less, a polarizing plate having a boric acid cross-linking degree of 3.3 or less can be produced more efficiently.
[0182] Example
[0183] The present invention will be described in more detail below with reference to Examples. "%" and "parts" in Examples are by mass % and by mass parts unless otherwise specified.
[0184] <Measurement Method and Evaluation Method>
[0185] (1)Thickness of polarizer
[0186] The thickness of the polarizing plate obtained in each of Examples and Comparative Examples was measured using a digital micrometer MH-15M manufactured by Nikon Corporation.
[0187] (2) Degree of crosslinking
[0188] A sample for measurement was cut out from the center of the polarizing plate obtained in each example and comparative example into a size of 10 cm×10 cm, and the degree of crosslinking of the sample was measured using a Cary 660 (FT-IR) apparatus manufactured by Agilent Technologies.
[0189] Using Specac's Golden Gate (ATR) diamond crystal, the scanning frequency was 16 times and the resolution was 2 cm -1 under the conditions of.
[0190] In addition, the IR data measured will be based on 2500cm -1 Above and 3700cm -1The following is set as the baseline of 2900cm -1 Above and 2920cm -1 The maximum value height in the following region is taken as the reference peak height. -1 Above and 1520cm -1 The following is set as 1280cm when the baseline -1 Over 1295cm -1 The height of the maximum value in the region below 1280 cm is divided by the height of the reference peak. -1 Over 1295cm -1 The peak in the following region is derived from the BO bond. This value is taken as the cross-linking degree.
[0191] Degree of crosslinking = (1280cm -1 Over 1295cm -1 The height of the maximum value below) / (the height of the reference peak)
[0192] The above-mentioned method for measuring the degree of crosslinking was performed three times, and the average value was calculated.
[0193] (3) Visibility correction single transmittance and visibility correction polarization degree
[0194] The linear polarized light from the prism is incident on the polarizer, and the measurement is performed using a spectrophotometer with an integrating sphere (manufactured by JASCO Corporation, V7100). The MD transmittance and TD transmittance are calculated within the wavelength range of 380nm to 780nm, and the monomer transmittance and polarization degree at each wavelength are calculated according to the following formula (A) and formula (B). Furthermore, the visibility correction is performed using the 2-degree field of view (C light source) of JISZ8701 to calculate the visibility-corrected monomer transmittance (Ty) and the visibility-corrected polarization degree (Py). It should be noted that "MD transmittance" refers to the transmittance when the direction of the polarized light from the Glan-Thompson prism is parallel to the transmission axis of the polarizing plate sample. In formula (A) and formula (B), "MD transmittance" is indicated as "MD". In addition, "TD transmittance" refers to the transmittance when the direction of the polarized light from the Glan-Thompson prism is orthogonal to the transmission axis of the polarizing plate sample. In the formula (A) and the formula (B), “TD transmittance” is indicated as “TD”.
[0195] Visibility correction single transmittance (%) = (MD + TD) / 2 ... (A)
[0196] Visibility corrected polarization degree (%) = {(MD-TD) / (MD+TD)}×100…(B)
[0197] (4) Sealing force
[0198] A test piece with a width of 25 mm and a length of about 170 mm was cut out from the polarizing plate obtained in each embodiment and comparative example. A tensile testing machine [manufactured by Shimadzu Corporation, AUTOGRAPH AGX-50NX testing machine] was used to clamp one end of the test piece in the length direction. A 180° peel test based on JIS K6854-2: "Adhesives - Peel Adhesion Strength Test Method - Part 2: 180-degree peeling" was performed at a crosshead speed of 300 mm / min (clamp moving speed) at a temperature of 23°C and a relative humidity of 60%. The peeling force when peeling off the first protective film 13a from the test piece was measured. The peeling force when peeling off the first protective film 13a was taken as the adhesion force.
[0199] <Examples and Comparative Examples>
[0200] (Production of Polarizing Plate A)
[0201] A long polyvinyl alcohol film (average degree of polymerization: about 2400, degree of saponification: 99.9 mol % or more, thickness: 60 μm) was continuously conveyed and immersed in a swelling bath containing pure water at 30° C. for a residence time of 50 seconds (swelling step).
[0202] Next, the film extracted from the swelling bath was immersed in a dyeing bath containing iodine at a ratio of potassium iodide / water of 2 / 100 (mass ratio) at 30° C. for a retention time of 60 seconds (dyeing step).
[0203] Next, the film extracted from the dyeing bath was immersed in a first crosslinking bath of potassium iodide / boric acid / water at 12 / 3.0 / 100 (mass ratio) and 56° C. for a residence time of 40 seconds (first crosslinking step).
[0204] Next, the film was immersed in a second crosslinking bath of potassium iodide / boric acid / water at 8.9 / 2.49 / 100 (mass ratio) and 40° C. for a residence time of 6 seconds (second crosslinking step).
[0205] In the dyeing step, the first cross-linking step, and the second cross-linking step, longitudinal uniaxial stretching was performed by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was set to 6 times.
[0206] Next, the film extracted from the cross-linking bath was immersed in a cleaning bath containing pure water at 5° C. for a residence time of 1 second (cleaning step).
[0207] The resulting product was introduced into a drying oven at 78° C. for a residence time of 100 seconds and dried to obtain a polarizing plate A (drying step).
[0208] The thickness of the polarizing plate A obtained as described above was 24 μm. The degree of boric acid crosslinking of the polarizing plate A obtained as described above was measured and found to be 3.12.
[0209] (Preparation of Polarizing Plate B)
[0210] A long polyvinyl alcohol film (average degree of polymerization: about 2400, degree of saponification: 99.9 mol % or more, thickness: 60 μm) was continuously conveyed and immersed in a swelling bath containing pure water at 30° C. for a residence time of 50 seconds (swelling step).
[0211] Next, the film extracted from the swelling bath was immersed in a dyeing bath containing iodine at a ratio of potassium iodide / water of 2 / 100 (mass ratio) at 30° C. for a retention time of 60 seconds (dyeing step).
[0212] Next, the film extracted from the dyeing bath was immersed in a first crosslinking bath of potassium iodide / boric acid / water at 12 / 4.1 / 100 (mass ratio) and 58° C. for a residence time of 40 seconds (first crosslinking step).
[0213] Next, the film was immersed in a second crosslinking bath of potassium iodide / boric acid / water at 8.49 / 2.49 / 100 (mass ratio) and 40° C. for a residence time of 6 seconds (second crosslinking step).
[0214] In the dyeing step, the first cross-linking step, and the second cross-linking step, longitudinal uniaxial stretching was performed by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was set to 6 times.
[0215] Next, the film extracted from the second cross-linking bath was immersed in a cleaning bath containing pure water at 5° C. for a residence time of 1 second (cleaning step).
[0216] The resulting product was introduced into a drying oven at 78° C. for a residence time of 100 seconds and dried to obtain a polarizing plate B (drying step).
[0217] The thickness of the polarizing plate B obtained in the above manner was 24 μm. The degree of boric acid crosslinking of the polarizing plate B obtained in the above manner was measured and found to be 3.45.
[0218] (Production of Polarizing Plate C)
[0219] A long polyvinyl alcohol film (average degree of polymerization: about 2400, degree of saponification: 99.9 mol % or more, thickness: 60 μm) was continuously conveyed and immersed in a swelling bath containing pure water at 30° C. for a residence time of 50 seconds (swelling step).
[0220] Thereafter, the film extracted from the swelling bath was immersed in a dyeing bath containing iodine at a ratio of potassium iodide / water of 2 / 100 (mass ratio) at 30° C. for a retention time of 60 seconds (dyeing step).
[0221] Next, the film extracted from the dyeing bath was immersed in a first crosslinking bath of potassium iodide / boric acid / water at 12 / 3.9 / 100 (mass ratio) and 57.5° C. for a residence time of 40 seconds (first crosslinking step).
[0222] Next, the film was immersed in a second crosslinking bath of potassium iodide / boric acid / water at a ratio of 9.0 / 3.5 / 100 (mass ratio) and a temperature of 40° C. for a residence time of 6 seconds (second crosslinking step).
[0223] In the dyeing step, the first cross-linking step, and the second cross-linking step, longitudinal uniaxial stretching was performed by stretching between rolls in a bath (stretching step). The total stretching ratio based on the original film was set to 6 times.
[0224] Next, the film extracted from the second cross-linking bath was immersed in a cleaning bath containing pure water at 5° C. for a residence time of 1 second (cleaning step).
[0225] The resulting product was introduced into a drying oven at 78° C. for a residence time of 100 seconds and dried to obtain a polarizing plate C (drying step).
[0226] The thickness of the polarizer C obtained as described above was 24 μm. The degree of boric acid crosslinking of the polarizer C obtained as described above was measured to be 3.58.
[0227] <Preparation of Active Energy Ray-Curing Adhesive>
[0228] The cation-curable components shown below were mixed to prepare an ultraviolet-curable adhesive as an active energy ray-curable adhesive.
[0229] 3',4'-Epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate (trade name: CEL2021P, manufactured by Daicel Corporation): 70 parts by mass
[0230] Neopentyl glycol diglycidyl ether (trade name: EX-211, manufactured by Nagase ChemteX): 20 parts by mass
[0231] 2-Ethylhexyl glycidyl ether (trade name: EX-121, manufactured by Nagase ChemteX): 10 parts by mass
[0232] Cationic polymerization initiator (trade name: CPI-100, 50% solution, manufactured by SAN-APRO): 4.5 parts by mass (substantial solid content: 2.25 parts by mass)
[0233] <Preparation of protective film>
[0234] The following two types of protective films were prepared.
[0235] (First protective film)
[0236] The first protective film was a 45 μm thick matte hard-coated triacetate cellulose film "AGSR 16H" (trade name) manufactured by Dai Nippon Printing Co., Ltd.
[0237] (Second protective film)
[0238] The second protective film was a 50 μm thick cyclic polyolefin resin film “ZB12” (trade name) manufactured by ZEON Corporation of Japan.
[0239] <Production of Polarizing Plate>
[0240] (Example 1)
[0241] like Figure 1 As shown, the surface of the first protective film 13a not subjected to matte hard coating and the surface of the second protective film 13b are subjected to corona treatment. An ultraviolet curable adhesive is applied to the corona treated surfaces of the first protective film 13a and the second protective film 13b and bonded to both sides of the polarizer A.
[0242] Through the above steps, a laminated body including the first protective film 13 a / ultraviolet curing adhesive / polarizer 11 / ultraviolet curing adhesive / second protective film 13 b is produced.
[0243] Next, an ultraviolet irradiation device with a conveyor belt (the lamp used was "DBULB" manufactured by FUSION UV SYSTEMS) was used to irradiate the second protective film 13b with a cumulative light intensity of 250 mJ / cm 2 Thus, the polarizing plate 10 having the adhesive layer 12 obtained by curing the ultraviolet curing adhesive was obtained. The thickness of the adhesive layer 12 was 3 μm.
[0244] The second protective film 13 b surface of the polarizing plate 10 was subjected to a corona treatment, and a 25 μm thick adhesive (“P-3132” (product name) manufactured by LINTEC) was bonded thereto to prepare a polarizing plate with an adhesive layer.
[0245] The polarizing plate 10 with an adhesive layer produced in this way was cut into 200 mm × 25 mm with the absorption axis direction of the polarizer as the long side, and the polarizing plate 10 was bonded to the soda glass. Furthermore, the first protective film 13a and the polarizer 11 were partially peeled off by a cutter to produce a sample for adhesion evaluation. The adhesion evaluation sample was used to measure the adhesion by the above method.
[0246] (Comparative Example 1)
[0247] A polarizing plate 10 with an adhesive layer was obtained in the same manner as in Example 1 except that the polarizing plate B was used instead of the polarizing plate A, and the adhesion was measured.
[0248] (Comparative Example 2)
[0249] A polarizing plate 10 with an adhesive layer was obtained in the same manner as in Example 1 except that the polarizing plate C was used instead of the polarizing plate A, and the adhesion was measured.
[0250] [Table 1]
[0251]
[0252] Table 1 shows that the adhesion of polarizing plates produced using polarizers B and C of Comparative Examples 1 and 2 is 0.36 N / 25 mm and 0.34 N / 25 mm, respectively. In contrast, the adhesion of polarizing plates produced using polarizer A of Example 1 is 0.54 N / 25 mm, indicating that the adhesion between the polarizer and the protective film is improved.
Claims
1. A polarizing plate, which is obtained by adsorbing a dichroic dye on a polyvinyl alcohol-based resin film and orienting it, The boric acid crosslinking degree of the polarizer is 3.3 or less, Visibility correction single unit transmittance is more than 40%, The visibility-corrected polarization degree is above 99.98%. 2 . A polarizing plate comprising the polarizing plate according to claim 1 , wherein a protective film is provided on at least one surface of the polarizing plate.
3. The polarizing plate according to claim 2, further comprising a laminating layer for laminating the polarizer and the protective film, The lamination layer is a layer obtained by curing an active energy ray-curable adhesive.
4. A method for manufacturing a polarizing plate, wherein: The polarizer is obtained by adsorbing a dichroic pigment on a polyvinyl alcohol resin film and orienting the film. The manufacturing method includes the following steps: a dyeing step of dyeing the polyvinyl alcohol-based resin film with a dichroic pigment; a cross-linking step of cross-linking the polyvinyl alcohol-based resin film after the dyeing step; and a drying step of drying the polyvinyl alcohol-based resin film after the cross-linking step, The cross-linking process has the following steps: a first cross-linking step of immersing the polyvinyl alcohol-based resin film in a first cross-linking bath having a boric acid content of 4.0 parts by mass or less relative to 100 parts by mass of water; as well as The second cross-linking step is to immerse the polyvinyl alcohol-based resin film after the first cross-linking step in a second cross-linking bath having a boric acid content of 3.5 parts by mass or less relative to 100 parts by mass of water.
5. The method for manufacturing a polarizing plate according to claim 4, wherein: The temperature of the first cross-linking bath is 60° C. or lower, and the temperature of the second cross-linking bath is 45° C. or lower.
6. A method for manufacturing a polarizing plate, comprising the following steps: A step of manufacturing a polarizing plate by the manufacturing method according to claim 4 or 5; and A laminating step of laminating a protective film on one or both sides of the polarizer via a laminating layer.
Citation Information
Patent Citations
Production of polarizing film
JP1994281816A
Production of polarizer film
JP1998153709A
Method of manufacturing polarizing film, and manufacturing device
JP2022136978A